Combining Acceptance and Commitment Therapy With Adventure Therapy to Promote Psychological Wellbeing for Children At-Risk - Tracey, Danielle; Gray, Tonia; Truong, Son; Ward, Kumara (Frontiers in Psychology, 2018)
Both Acceptance and Commitment Therapy and Adventure Therapy are emerging as popular strategies to elevate psychological wellbeing. The potential benefits of combining both approaches, however, remains underexplored. For children at-risk, the combination of the two approaches may provide the opportunity to benefit from Acceptance and Commitment Therapy through Adventure Therapy where the former’s typical mode of delivery may minimize engagement. This small-scale intervention study focuses on nine upper primary school-aged children enrolled in a specialist school in Australia for children with challenging behavior and/or emotional needs. Participants completed a newly-developed eight-week intervention entitled ‘ACT in the Outdoors’ which combined key principles of both Acceptance and Commitment Therapy and Adventure Therapy. The impact of the intervention was assessed via a combination of pre and post participant psychological measures, and post interviews with participants and teachers. The results highlight improvements in psychological wellbeing and skill development for a portion of the participating children. Improvements appear to be mitigated by attendance and level of psychological wellbeing upon program entry. Results suggest that more research is warranted to further understand the potential benefit of this innovative interdisciplinary approach.